Teacher’s ICT competence: requirements and ways to develop - Gapparov , Abdujalil (The Lingua Spectrum, 2025)
This article analyzes the content of a teacher’s information and communication technologies (ICT) competence, modern requirements for it, and ways to form and develop it. At a time when the digital transformation process is fundamentally changing the education system, a teacher’s readiness to work with ICT, technological literacy, and skills in the effective use of digital tools are becoming an important factor for the quality of education. The article highlights the main requirements for a teacher’s ICT competence – based on skills such as the use of technical tools, working on educational platforms, digital pedagogy, Internet security, digital culture, and information analysis. It also highlights the role of training seminars, practical training, online courses, and mentoring programs in the development of this competence. The study puts forward proposals aimed at increasing the digital literacy of teachers based on practical examples from the education system of Uzbekistan. In particular, it is emphasized that it is important to develop comprehensive approaches to the development of ICT competence in the training of pedagogical personnel and their integration into the continuous education system. This article is aimed at improving the processes of training and retraining of pedagogical personnel in the context of digitalization of education and serves as a theoretical and practical resource for teachers, trainers, methodologists and researchers in the field.